703 From in-lab to at-home: Measuring sleep and memory in the time of SARS-COVID-19. (3rd May 2021) - Mullins, Anna; Parekh, Ankit; Kam, Korey; Schoenholz, Reagan; Valencia, Daphne; Roberts, Zachary; Castillo, Bresne; Rapoport, David; Ayappa, Indu; Osorio, Ricardo; Varga, Andrew
Abstract: Introduction: The SARS-COVID-19 pandemic restricted in-lab research activities especially in older individuals who are considered at-risk for severe disease. To continue longitudinal sleep research in this population we sought to test the feasibility of remotely conducting at-home sleep and memory research and to compare two ambulatory polysomnography (PSG) devices for ongoing home sleep testing. Methods: 20 older (age=65.6±5.5 years) cognitively normal adults (65% female) who had previously undergone 2 nights in-lab sleep, memory and vigilance testing were delivered equipment for 2 nights at-home, technician-guided remote PSG set-up (1 night each for Somté [EEG: Fp1-M2, Cz-M1] and Sleep Profiler (SP) [EEG: Fp1-Fp2] devices- randomized presentation), and 6 timed trials on a 3D spatial maze navigation memory plus morning psychomotor vigilance testing (PVT). The night-to-night differences for devices and in-lab versus at-home testing environments were compared for sleep macro and EEG microarchitecture using paired Wilcoxon rank sum and t-tests where appropriate. First-night maze completion time (CT) and PVT reaction time and lapses were also compared. Results: 19 people completed 2 nights at-home PSG, 18 completed PVT and 9 completed all 6 maze trials. Quality frontal EEG signals were obtained for 16 SP and 11 Somté recordings. There was no significant night to night differences (night 1–night 2) between in-lab and at-home environments for total sleep time (mean difference: in-lab= -0.27 vs at-home = 0.35 hours), wake after sleep onset (WASO) (median difference: in-lab= 3.0 vs at-home = 0.7 %WASO), or slow wave sleep (SWS) (mean difference: in-lab= -0.70 vs at-home = 2.3 %SWS). Relative frontal slow wave activity and spindle density were not significantly different between devices or environments. K-complex density (SP= 1.0 vs Somté =2.7/minNREM2, p=0.004) was significantly reduced with the SP device compared to Somté devices. There were no significant differences for maze CT and PVT measures between in-lab and at-home environments. Conclusion: The night-to-night differences in sleep macroarchitecture do not appear to be influenced by environment or device however measures of EEG microstructure such as K-complexes, which are amplitude-dependent, may be underestimated with the Sleep Profiler device due to smaller EEG amplitude from a derivation with short inter-electrode distances. Support (if any): NIH (R01AG056031, R01AG056531, K24)